GAMBARAN KEBIASAAN MAKAN, AKTIVITAS FISIK,BODY IMAGE, DAN STATUS GIZI REMAJA PUTRI DI SMK NEGERI 2 SIBOLGA - Desty Adinda; Etti Sudaryati; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The eating habits of adolescents now consume more calories in excess accompanied by a lack of physical activity causes many of the adolescents with overweight and obesity status. Adolescence is closely related with self-actualization. One was about body image in adolescents will greatly affect eating habits, actually selection of groceries and food frequency. This study aims to describe eating habits, physical activity, body image, the nutritional status of female adolescent in SMK Negeri 2 Sibolga. This type of research was observational with cross sectional design. This study was conducted by assess the food frequency questionnaire, food type, calculate nutrient intake using a 24-hour food recall. Calculating physical activity with PAL and nutritional status with BMI / U. Body image was measured by using the method of Figure Rating Scale (FRS). The research sample were 90 people who the adolescent girls. Body weight was measured using scales student and student body height using microtoise. Data analysis used descriptive analysis. The results of study showed most of eating habits of female adolescent in good categories as much as 98.0%, 63.3% female students the kind of food is not varied, 95,6% the energy consumption not correspond of RDA, 71,1% protein consumption not correspond of RDA, 87,8% the fat consumption not correspond RDA, and 91,1% the carbohydrate not correspond of RDA. Physical activity students 77.8% mild category. Negative of Body image is 56.7%. The nutritional status of students skinny 5.6%, 14.4% fat and 5.6% obese. Students is expected to have paid more attention to his eating habits by adopting appropriate diet with Balanced Nutrition Guidelines. Schools should have a partnership with health centers to information disseminated regarding weight and height normal, so students not mistaken represent nutrition own status, so they do not have a negative body image. Keywords: Eating Habits, Physical Activity, Nutritional Status, Body Image, Female Adolescents